Memories Of The First President Of The Academy Of Medical Sciences - Professor Aurel Moga - Baltă, Nicolae (Medicine and Pharmacy Reports, 2014)
This year marks 110 years since the birth of Professor Aurel Moga, member of the Romanian Academy, and it is the best time for the Medical School in Cluj-Napoca to bring homage to the brilliant representative of Romanian medicine, as well as a very good opportunity for me to evoke the first President of the Academy of Medical Sciences.